PENGARUH MOTIVASI, KEMAMPUAN KERJA DAN IKLIM KERJA TERHADAP KINERJA DOSEN PADA FAKULTAS EKONOMI UNIVERSITAS TRIDINANTI PALEMBANG - Zakiah . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2015)
The aim of this report is to know how the effect of Motivation, Work Ability and Working Environment on Lecture Performance in Economic Faculty of The Tridinanti University Palembang. The data collected by Questioner. The Total of Population is 39 People. The data were analyzed by using quantitative descriptive analyzes with SPSS Program.From the processing of the data obtained coefficients regression for Variable Motivation (X1) is 0,270, the coefficients regression for Work Ability (X2) is 0,342, and the coefficients regression for Working Environment (X3) is 0,398, while the constant value is 0,668, so the Multiple Regression Equation research are:Ý = 0,668 + 0,270X1 + 0,342X2 + 0,398X3The result of Assumption show that the effect of Motivation, Work Ability and Working Environment together with Lecture Performance in Economic Faculty Of The Trdinanti University is F sig 0,000 0,000 ≤ 0,05, and the result of Assumption 2, Assumption 3 and Assumption 4 show the effect as one by one, that are t sig 0,002; 0,009 and 0,018 ≤ 0,05 Keyword : Motivation, Work Ability , Working Environment , Lecture Performance